Kunst für den Bund. - Städtische Kunstmuseum Bonn (Bonn : VG Bild-Kunst, 1981)
Albert, Hermann ; Albrecht, Joachim ; Antes, Horst : Asmus, Dieter ; Backe, Burkard ; Banakar-Bund, Christa ; Baschang, Hans ; Baukhage, Gerd ; Baumeister, Willi ; Becher, Bernhard und Hilla ; Berner, Bernd ; Bernhard, Franz ; Beuys, Joseph ; Bindl, Andreas ; Bingemer, Karl B. ; Bonato, Victor ; Bräckle, Jakob ; Bramke, Erdmut ; Bremer, Alexander ; Breuer, Leo ; Brodwolf, Jürgen ; Brüning, Peter ; Buchheister, Carl ; Buchholz, Erich ; Bühl, Hede ; Cavael, Rolf ; Cimiotti, Emil ; etc.
Kunst für den Bund, Städtische Kunstmuseum Bonn, 24. November '81 - 10. Januar '82
boek